Design of GaN-Based Low-Loss Y-Branch Power Splitter - Purnamaningsih, Retno Wigajatri; Saraswati, Irma; Poespawati, Nji Raden; Dogheche, Elhadj (Makara Journal of Technology, 2014)
We present a Y-branch power splitter design with a multimode section using GaN on Sapphire at telecommunication wavelength. The GaN sample optical properties were also investigated, resulting in a refractive index for the GaN layers nTE=2.289±0.001 and nTM=2.324±0.00. Optimization of the structure parameters for this structure was conducted accurately using BPM methods. The results demonstrated the possibility of realizing a GaN-based Y-branch power splitter for various applications.